C‐C chemokine receptor type 1 mediates osteopontin‐promoted metastasis in hepatocellular carcinoma. Issue 3 (13th February 2018) - Zhu, Ying; Gao, Xiao‐Mei; Yang, Jing; Xu, Da; Zhang, Yu; Lu, Ming; Zhang, Ze; Sheng, Yuan‐Yuan; Li, Jian‐Hua; Yu, Xin‐Xin; Zheng, Yan; Dong, Qiong‐Zhu; et al.
Abstract : In the hepatocellular carcinoma (HCC) microenvironment, chemokine receptors play a critical role in tumorigenesis and metastasis. Our previous studies have found that osteopontin (OPN) is a promoter for HCC metastasis. However, the role of chemokine receptors in OPN‐induced HCC metastasis remains unclear. In this study, we demonstrate that OPN is dramatically elevated in HCC tissues with metastasis and that high expression of OPN correlates with poorer overall survival and higher recurrence rate. OPN upregulates chemokine receptor expression, migration, invasion and pulmonary metastasis in HCC. We find that C‐C chemokine receptor type 1 (CCR1) and C‐X‐C chemokine receptor type 6 (CXCR6) are the most upregulated chemokine receptors induced by OPN. CCR1 knockdown results in reduction of migration, invasion and pulmonary metastasis induced by OPN in vitro and in vivo, whereas CXCR6 knockdown does not reverse OPN‐promoted migration and invasion. Moreover, OPN upregulates the expression of CCR1 through activating phosphoinositide 3‐kinase (PI3K)/AKT and hypoxia‐inducible factor 1α (HIF‐1α) in HCC cells. Furthermore, blockade of OPN‐CCR1 axis with CCR1 antagonist significantly restrains the promoting effects of OPN on HCC progression and metastasis. In human HCC tissues, OPN expression shows significantly positive correlation with CCR1 expression, and the patients with high levels of both OPN and CCR1 have the most dismal prognosis. Collectively, our results indicate that the OPN‐CCR1 axis in HCC is important for accelerating tumor metastasis and that CCR1 is a potential therapeutic target for controlling metastasis in HCC patients with high OPN. Abstract : In this study, we found that OPN up‐regulated the expression of C‐C chemokine receptor‐1(CCR1) via activating phosphoinositide 3‐kinase (PI3K)/AKT and hypoxia‐inducible factor 1α(HIF‐1α). Moreover, blockade of OPN/CCR1 signaling with CCR1 antagonist significantly restrained the promoting effects of OPN on HCC progression and metastasis. Our work proved that CCR1 may be a potential therapeutic target for controlling metastasis in HCC patients with high OPN.